A comparison of desflurane and sevoflurane in the recovery of cognitive function after general anesthesia in elderly patients - Jadhav, Pandurang Kondiba (International Journal of Research in Medical Sciences, 2017)
Background: The postoperative cognitive dysfunction (POCD) or psychomotor function disorder is known to be associated with the anesthetic agents, as well as the physiological changes resulting from the anesthesia. The known risk factors are old age, preexisting cerebral cardiac or vascular disease, alcohol abuse, intra and post-operative complications. Methods: 50 patients above 65 years of age falling into ASA Grade 1, 2, or 3 were catagrzed into 2 groups, one (Group A) wherein sevoflurane was given as the anesthetic agent and the other (Group B) where desflurane was administered. All had undergone physical and regular blood examination. MMSE score was taken for all patients for cognitive recognition before surgery and 1, 3, and 6 hours after surgery. Results: Of the 50 patients, the MMSE score was above 27 for all before surgery, while, post-surgery it was below 27 after I hour in 100% of the cases. After 3 hours, in Group A, the mean MMSE was above 27 while it was still below 27 in Group B while it was above 27 in both the Groups after 6 hours post-surgery. There was only 1 cases of POCD after 6 hours in Group A and none in Group B. The recovery time was faster in Group B as compared to Group A. Conclusions: Desflurane was marginally a better anesthetic agent in terms or recovery to sevoflurane and sevoflurane was slightly better than the former when it came to cognitive recognition Therefore, we conclude that both the drugs are equally good anesthetic agents.